The Drug Excipient Cyclodextrin Interacts With -Luciferin and Interferes With Bioluminescence Imaging - Jeyan S. Kumar MSc; Lisa M. Miller Jenkins PhD; Michael M. Gottesman MD; Matthew D. Hall PhD (Molecular Imaging, 2016)
Cyclodextrins are well-characterized, barrel-shaped molecules that can solubilize organic small molecules in aqueous solution via host–guest interactions. As such, cyclodextrins are used as excipients for experimental therapeutics in vivo. We observed unanticipated modifications to bioluminescence imaging (BLI) signal intensity when 2-hydroxy-propyl-β-cyclodextrin (HPCD) was coinjected as an excipient. We hypothesized that HPCD binds d -luciferin and interferes with the BLI signal. Using luciferase-expressing cell lines, we showed that HPCD lowers the BLI signal in a concentration-dependent manner. Flow cytometry revealed that HPCD resulted in reduced cellular accumulation of d -luciferin, and mass spectrometry revealed d -luciferin HPCD species, confirming a direct interaction. In vivo imaging using a luciferase mouse model demonstrated that HPCD reduced luciferin-mediated BLI compared to luciferin alone. The implications of using HPCD as an excipient in BLI studies are discussed.